Amoxicillin, Ibuprofen, or Prednisolone Does Not Modify Post‐tonsillectomy Pain in Children: A Randomized Controlled Trial. (23rd August 2013) - Tamashiro, Edwin; Azevedo, Carolina B.; Carenzi, Lucas R.; Valera, Fabiana; Anselmo Lima, Wilma T.
Abstract : Objectives: Evaluate the effect of amoxicillin, ibuprofen, or prednisolone on post‐tonsillectomy pain in children. Methods: 225 children between 6‐10 years‐old undergoing cold knife adenotonsillectomy/tonsillectomy were included in the study. Pain was monitored in the first seven days after surgery by the parent's ("Parents' Post‐Operative Pain" ‐PPPM) and child's assignment ("Revised‐Facial Pain Scale" ‐R‐FPS). Pain was also indirectly analyzed by the number of analgesic administration and return to solid food intake. 45 children were randomized into 5 distinct groups, with the respective number of patients analyzed after losses and exclusions: 1) control n = 42; 2) amoxicillin 50mg/kg/day, n = 31; 3) oral prednisolone 0.5mg/kd/day, n = 30; 4) ibuprofen 5mg/kg/dose tid, n = 32; 5) amoxicillin plus prednisolone, n = 37. All groups received oral analgesics (dypirone and acetaminophen) to use as required. PPPM was analyzed by a linear regression model with mixed effects with Tukey post‐test for multiple comparisons (SAS 9.0). R‐FPS and analgesic intake were analyzed by Kruskal‐Wallis. Return to solid intake was analyzed by Wilcoxon test, considering significant when P < 0.05. Results: Multiple comparisons demonstrated that the evolution of pain, matched day‐per‐day among the different groups, was not statistically different either by PPPM or R‐FPS ( P > 0.05). The number of analgesic intake was also similar in all groups ( P = 0.10) as well as the return to solid food intake ( P = 0.41). Also, all groups presented a similar standard of clinical improvement in intervals of two days ( P < 0.01). Conclusions: Our data demonstrate that the addition of amoxicillin, ibuprofen, or prednisolone to simple analgesic prescription does not modify post‐tonsillectomy pain in children.